Effects of Behavioral Counseling on Modeling Techniques Improving Self Achievment - Amelia Nur Setianingsih; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2018)
This study aims to determine the effect of behavioral counseling with modeling techniques to improve the self achievement of students and differences in self achievement of students who are given behavioral counseling techniques and modeling that is not given to students of class XI IPB SMAN 1 Sukasada. The population of this study is all students of class XI SMAN 1 Sukasada. The sample of this research is determined by random sampling technique with the number of sampling 21 students from the experimental class. Method of data collection in research using observation method, interview, diary, and questionnaire self achievment Likert scale method of data analysis method for hypothesis test using t-test. The result of this research indicate that there is influence of behavioral counseling technique of modeling to self achievement to students of class XI IPB SMAN 1 Sukasada, and there are differences of self achievment given behavioral counseling technique modeling with which not given.